2014
DOI: 10.1520/mpc20130023
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Characterization of a Nanocarbon Infused Aluminum-Matrix Composite

Abstract: A nanocarbon-infused aluminum-matrix composite, termed "covetic," has been developed by Third Millennium Metals, LLC, and we have evaluated the enhanced performance prospects for strength and electrical conductivity. This paper examines the effects of the nanoscale carbon on the physical, electrical and mechanical properties of the metal-matrix composite based on microscopy, hardness, quasi-static tensile strength, high strain-rate compression strength and electrical conductivity measurements. In the as-extrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…However, the hardness measured by nanoindentation and Vickers measurement indicated a higher value for the sample with 5% than 3% carbon [18] . Similar results have been reported for as-extruded Al 6061 covetic with 3 wt.% C which shows a 30 % increase in ultimate tensile strength compared to a pure as-extruded Al 6061 with no C [19].…”
Section: Tensile Strength Of Al Coveticsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the hardness measured by nanoindentation and Vickers measurement indicated a higher value for the sample with 5% than 3% carbon [18] . Similar results have been reported for as-extruded Al 6061 covetic with 3 wt.% C which shows a 30 % increase in ultimate tensile strength compared to a pure as-extruded Al 6061 with no C [19].…”
Section: Tensile Strength Of Al Coveticsupporting
confidence: 87%
“…Namely, the ultimate tensile strength increased by 40% and hardness increased over 30% for 5% C in Al-7075 compared with pure Al-7075 [18]. Also, adding carbon to Al-6061 to make Al-6061 cv 3% improved the tensile strength and hardness of as-extruded Al-6061 cv 3% compared to pure as-extruded Al-6061 by 23-30% and the electrical conductivity increased by 43% [19]. Thus, adding C improved the mechanical and electrical properties of the alloy in addition to the already high weld ability and anti-corrosion properties of the parent alloys.…”
Section: Introductionmentioning
confidence: 99%
“…5 Balachandran et al 6 examined the properties of covetically processed Cu with a nominal concentration of 3wt.% C and found no significant difference in density between the pure Cu control specimen (8.91 g/cc) and the 3wt.% C material (8.89 g/cc) where based on nominal composition, rule-of-mixtures, and full density a density decrease of about 10% was expected; 6 the electrical conductivity of the 3wt.% material was about 6.8% higher than the pure Cu control. Density measurements by Brown et al 7 were similarly unable to confirm the presence of C in their covetically processed aluminum samples; the slight departures of their samples from theoretical full density were likely due to void fraction. 7 After T6 heat treatment, Brown's covetic sample had the same electrical conductivity as the sample without C added.…”
mentioning
confidence: 87%
“…Density measurements by Brown et al 7 were similarly unable to confirm the presence of C in their covetically processed aluminum samples; the slight departures of their samples from theoretical full density were likely due to void fraction. 7 After T6 heat treatment, Brown's covetic sample had the same electrical conductivity as the sample without C added. The high conductivity of Brown's as-extruded covetic sample needs to be repeated due to likely errors caused by short sample length, larger sample diameter, and the resulting low resistance; the as-extruded sample results were also not consistent with the other conductivity measurements or density results.…”
mentioning
confidence: 87%
“…It is being reported that those composites have higher electrical and mechanical properties, corrosion resistance, thermal conductivity, and other properties. [7,8,[13][14][15][16][17][18] The inventor of the metallurgical production method of nanocomposite materials called ''Covetic'' is Third Millennium Materials, LLC (Dayton, Ohio). Historically, the incorporation of carbon into metals that are not strong carbide formers (like Al, Cu, Ag, Au, Sn, Zn, and Pb) has been technologically difficult because of low carbon wettability.…”
Section: Introductionmentioning
confidence: 99%